2019
DOI: 10.1111/iep.12314
|View full text |Cite
|
Sign up to set email alerts
|

Co‐expression of TLR‐9 and MMP‐13 is associated with the degree of tumour differentiation in prostate cancer

Abstract: Summary In vitro experiments demonstrated that stimulation of Toll‐like receptor 9 (TLR‐9) by synthetic TLR‐9 ligands induces the invasion of TLR‐9‐expressing prostate cancer cells through matrix metalloproteinase 13 (MMP‐13). However, the clinical value of TLR‐9 and MMP‐13 co‐expression in the pathophysiology of the prostate is unknown. In the study, we evaluated the expression levels and clinical significance of the TLR‐9 and MMP‐13 in a series of prostate tissues. One hundred and eighty prostate tissues inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Kalantari et al . 34 revealed the bipartite function of MMP13 and TLR-9, patients with the high expression of MMP13 and TLR-9 showed an advanced stage of PCa. The status of CRPC and medicine resistance are the hot potatoes for the clinical treatment of PCa patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Kalantari et al . 34 revealed the bipartite function of MMP13 and TLR-9, patients with the high expression of MMP13 and TLR-9 showed an advanced stage of PCa. The status of CRPC and medicine resistance are the hot potatoes for the clinical treatment of PCa patients.…”
Section: Discussionmentioning
confidence: 96%
“…Ganguly et al [33] found that Notch3 could promote the bone metastasis of PCa patients throng MMP3 mediated osteoblastic lesion formation. Kalantari et al [34] revealed the bipartite function of MMP13 and TLR-9, patients with the high expression of MMP13 and TLR-9 showed an advanced stage of PCa. The status of CRPC and medicine resistance are the hot potatoes for the clinical treatment of PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have reported associations between expression and PrCa [ 46 ], including grade/stage [ 105 , 139 ] and metastatic properties, with MMP-1 ablation shown to reduce invasion [ 154 ]. Similarly, MMP-13 expression has typically not been associated with PrCa [ 31 , 48 , 84 , 91 , 95 ], but some studies do provide evidence of this [ 50 , 52 , 70 ]. Publications investigating MMP-11 also range from identifying no correlation [ 91 ] to a negative correlation [ 83 ] to a positive correlation [ 45 , 48 ], while the only study on MMP-23 points toward a negative correlation [ 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overall median age of these three groups was 66 years, which is the range from 48 to 90 years. Serum PSA levels in PCa patients (before surgery and receiving systemic treatment) were divided into three groups: less than 4 ng / ml, between 4 and 10 ng / ml, and more than 10 ng / ml (range 6-352, median :9 ng/mL) (20). Of the 90 PCa patients whose PSA level information was available, 6 cases (6.7%) had a PSA of < 4 ng / ml, 46 cases (51.1%) 4 to 10 ng / ml and 38 cases (42.2%) > 10 ng / ml.…”
Section: Study Populationmentioning
confidence: 99%